DEVELOPMENT OF MARKETING IN THE CONTEXT OF A TOURISM PANDEMIC IN UZBEKISTAN - Muhammadabad Dilovar Ramazonovma (Research Trend in Technology and Management, 2023)
The article analyzes the basic foundations of marketing in tourism. The author analyzed the methodology of tourism marketing, which is relevant in the conditions of the modern market after the pandemic. Based on theoretical materials and practical research by leading scientists in this field, as a result of the article, conclusions were drawn regarding the development of marketing in tourism at the stage of informatization of society and globalization of the market in Uzbekistan. The article formulates specific areas of current research in the field of tourism marketing for the pandemic period. And also the article discusses the conceptual foundations of marketing in the tourism industry, its features, functions, the need to use modern information technologies.